PENINGKATAN KEMAMPUAN MENGHITUNG OPERASI HITUNG CAMPURAN MELALUI MODEL PEMBELAJARAN OPEN ENDED PADA SISWA KELAS IV SDI ABABIL SUKODONO SIDOARJO - Yuniati, Katrien Rohmartiningsiwi (Journal Of Islamic Elementary School (JIES), 2017)
The ability to count on the mixed arithmetic operation material for the fourth grade students of SDI Ababil Sukodono Sidoarjo is still not optimal. This is caused by several factors, namely the lack of learning media, the learning process only uses the lecture method. Like a teacher telling students to immediately open the book they want to study and immediately without any motivation from the teacher. In response to this, learning will be carried out using an open-ended learning model through classroom action research. The purpose of this research is to know the application of the open-ended learning model on mixed arithmetic operations material and to know the increase in calculating ability in grade IV SDI Ababil Sukodono Sidoarjo after using the open ended learning model. The method used in this research is Classroom Action Research using the Kurt Lewin model which states that in one cycle there are four main steps, namely: Planning, Action or Action, Observing, and Reflecting . The research subjects were the fourth grade students of SDI Ababil Sukodono Sidoarjo, with a total of 28 students. The data collection techniques used were observation using teacher activity sheet instruments and student activity sheets, counting ability tests and documentation. The results of this study indicate that the application of the open-ended learning model can increase teacher and student activity in mathematics learning, it can be seen that the percentage of teacher activity increased in cycle I by 75.8% to 93.75% in cycle II, while the percentage of student activity from 70% in the first cycle to 87.5% in the second cycle. The open-ended learning model can improve the ability to calculate mathematics on mixed arithmetic operations material, this is indicated by the percentage of completeness of the calculating ability in cycle I reaching 73.57% and in cycle II reaching 100%, with a class average in cycle I of 84, 28% and the average cycle II was 88.9%.